2019
DOI: 10.3390/w11020194
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Landfill Leachates with Combined Acidification/Coagulation and the Fe0/H2O2 Process

Abstract: One of the major environmental concerns associated with waste disposal is the large amount of generated landfill leachates (LL), which are considered a type of wastewater with a complex composition. There is an urgent need to find an effective LL treatment method. LL were subjected to pretreatment followed by the Fe0/H2O2 process. Pretreatment efficiency was coagulation at pH 6.0 >> coagulation at pH 9.0 > acidification at pH 3.0. Coagulation at pH 6.0 in an optimal Fe3+ dose of 1000 mg/L decreased to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Amor et al (2015) [19] reported an increase in TOC removal from 54% with a single solar-photo-Fenton up to 75% using a coagulation pre-treatment with 2 g/L of FeCl 3 at pH = 5. Similarly, at pH = 3, Bogacki et al (2019) [38] achieved a total TOC removal of 75% combining coagulation with ferric chloride (1 g/L at pH = 6), and heterogeneous Fenton process (Fe 0 /H 2 O 2 = 1.4 ratio). However, a systematic comparison of coagulation with ferric chloride and alum as pretreatment for a photo-Fenton process has not been published yet.…”
Section: Youngmentioning
confidence: 98%
See 1 more Smart Citation
“…Amor et al (2015) [19] reported an increase in TOC removal from 54% with a single solar-photo-Fenton up to 75% using a coagulation pre-treatment with 2 g/L of FeCl 3 at pH = 5. Similarly, at pH = 3, Bogacki et al (2019) [38] achieved a total TOC removal of 75% combining coagulation with ferric chloride (1 g/L at pH = 6), and heterogeneous Fenton process (Fe 0 /H 2 O 2 = 1.4 ratio). However, a systematic comparison of coagulation with ferric chloride and alum as pretreatment for a photo-Fenton process has not been published yet.…”
Section: Youngmentioning
confidence: 98%
“…Furthermore, the use of ZVI allows working at neutral pH and can be reused several cycles [34,37]. Due to the high consumption of energy and chemicals for the direct use of AOPs without any pretreatment, the combination of coagulation/flocculation and AOPs seems to be the best option to treat the mature landfill leachates [19,38]. Amor et al (2015) [19] reported an increase in TOC removal from 54% with a single solar-photo-Fenton up to 75% using a coagulation pre-treatment with 2 g/L of FeCl 3 at pH = 5.…”
Section: Youngmentioning
confidence: 99%
“…Using 3 M hydrochloric acid (HCl) or 3 M sodium hydroxide, the pH of the samples was modified to the appropriate pH value (pH3–11) (NaOH). The acid and base used in this study were also used by other researchers, for example [ 29 , 30 ]. Then, using the pre-determined value of the operational condition, the leachate was agitated simultaneously.…”
Section: Methodsmentioning
confidence: 99%